Near-Field Antenna Measurements Using Photonic Sensor of Mach-Zehnder Interferometer - Masanobu Hirose; Satoru Kurokawa; Michitaka Ameya; Koji Komiyama (International Journal of Antennas and Propagation)
We have been developing a photonic sensor system to measure the electric near-field distribution at a distance shorter than one wavelength from the aperture of an antenna. The photonic sensor is a type of Mach-Zehnder interferometer and consists of an array antenna of 2.4 mm height and 2 mm width on a LiNbO3 substrate (0.5 mm thickness, 8 mm length, and 3 mm width) supported by a glass pipe. The photonic sensor can be considered to be a receiving infinitesimal dipole antenna that is a tiny metallic part printed on a small dielectric plate at microwave frequency. Those physical and electrical features make the photonic sensor attractive when used as a probe for near-field antenna measurements. We have demonstrated that the system can be applied to planar, spherical, and cylindrical near-field antenna measurements without any probe compensation approximately below 10 GHz. We show the theories and the measurements using the photonic sensor in the three near-field antenna measurement methods.